Doctor Down - N.V. Nagornaya; Ye.V. Bordyugova; N.A. Usenko (Zaslavsky O.Yu., 2013)
The article presents the biographical data of John Langdon Down, his invaluable contribution to the development of rehabilitation programs for children with Down syndrome. The basis of these programs was the socialization of people with intellectual disabilities. In doctor Down's rehabilitation center there were used methods, including health care, education, physical education, the formation of correct behavior.